2007
DOI: 10.1111/j.1439-0426.2006.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth and mortality of brown comber, Serranus hepatus (Linnaeus, 1758) (Pisces: Serranidae), in the eastern Adriatic (Croatian coast)

Abstract: Age, growth and mortality were analysed for brown comber, Serranus hepatus, collected in the eastern Adriatic from May 2002 to June 2003. Fish aged 2-7 years were present in the samples. Growth in length including both sexes was expressed using the von Bertalanffy equation, L ¥ ¼ 14.82, K ¼ 0.217 and t 0 ¼ )1.672. Age class 2, ranging in length from 5.8 to 9.0 cm TL, dominated the sample (29.3%). Total and natural mortality were Z ¼ 1.73 year )1 and M ¼ 0.63 year )1 , respectively. The exploitation rate, E ¼ 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In terms of body size, the maximum lengths of serranid species sensu stricto range widely (Love et al , ; Dulčić et al , ; Moore et al , ; Gomon et al , ). The majority of the ageing studies on serranids that have been based on validated ageing criteria, however, have typically yielded maximum ages of <20 years (Bubley, ; Tuset et al , ; Moore et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of body size, the maximum lengths of serranid species sensu stricto range widely (Love et al , ; Dulčić et al , ; Moore et al , ; Gomon et al , ). The majority of the ageing studies on serranids that have been based on validated ageing criteria, however, have typically yielded maximum ages of <20 years (Bubley, ; Tuset et al , ; Moore et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…They reported 62 species belonging to 3 major groups, decapods, amphipods, and fish, by analyzing stomach contents, and they added that decapods dominated the diet composition. Dulčić et al (2007) also stated that brown comber has been found in the stomachs of some commercial species such as Merluccius merluccius, Epinephelus marginatus, and Phycis phycis. In addition, according to Bilecenoğlu (2009), the brown comber is a carnivorous species, mostly consuming benthic decapod crustaceans, especially natantians and brachyurans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, according to Bilecenoğlu (2009), the brown comber is a carnivorous species, mostly consuming benthic decapod crustaceans, especially natantians and brachyurans. Although it has a widespread occurrence, brown comber is of low commercial value, probably because of its small size (Dulčić et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It inhabits sandy, muddy bottoms and sea grass meadows at depths ranging from 30 to 100 m (Tortonese, 1986;Golani et al, 2006). The species is very common in trawl catch compositions off the Adriatic and the Aegean Seas, and it is considered as discard by fishermen, probably because of its relatively small size (Dulčić et al, 2007;Bilecenoğlu, 2009). S. scriba and S. cabrilla are 2 species of the genus Serranus that inhabit the Black Sea (Bilecenoğlu et al, 2002;Keskin, 2010).…”
mentioning
confidence: 99%
“…The brown comber is a typical component of the biodiversity of the Aegean Sea and the Sea of Marmara, and it is one of the species discarded in trawl and beam trawl surveys (Dulčić et al, 2007;Bilecenoğlu, 2009). Mediterranization, the extension of Mediterranean fauna to the Black Sea, is an ongoing process and new records of Mediterranean-originated fauna for the Black Sea have been given by some scientists in recent years (Engin et al, 2007;Kovacic and Engin, 2009).…”
mentioning
confidence: 99%